Treatment of textile industry wastewater using dynamic membrane bioreactor: Impact of intermittent aeration on process performance - Sahinkaya, Erkan; Yurtsever, Adem; Cinar, Ozer (ELSEVIER SCIENCE BV, 2017)
This study aims at investigating the performance of intermittently aerated dynamic membrane bioreactor for the treatment of chromium containing synthetic textile wastewater. Nylon meshes with two different pore sizes, i.e. 20 mu m and 53 mu m, were tested. The bioreactor was operated under continuous or intermittent aeration conditions with aeration on/off durations of 5/3 min, 1/10 min, and 1/15 min. Although high suspended solid rejection was observed with the support layer having 20 mu m pore size, TMP quickly exceed 400-600 mbar, which caused increased suspended solid concentrations in the permeate. Whereas, when the support layer with 53 mu m pore size was used, the bioreactor was operated around 100 days without cleaning and with low permeate suspended solid concentration at fluxes of 23-29 LMH. In continuous aeration mode, color removal performance was negligible and the removal efficiency increased with lengthening unaerated period duration and reached 97%, when aeration on/ off duration was 1/15 min. In the dynamic layer, high molecular weight soluble organics were detected by gel permeation chromatographic analyses together with the identification of proteins and polysaccharides by the FT-IR analyses. SEM-EDS and metal analyses illustrated that inorganics may also have significant contribution to dynamic layer composition. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Dynamic membrane bioreactor; Intermittent aeration; Textile wastewater; Color removal; Membrane fouling; EXTRACELLULAR POLYMERIC SUBSTANCES; NONWOVEN FABRIC FILTER; REACTIVE-AZO-DYE; DENITRIFICATION PROCESSES; ANAEROBIC TREATMENT; CR(VI) REDUCTION; STABLE OPERATION; CAKE LAYER; GEL LAYER; FLUX; Engineering